Effect of Fermented Turmeric (Curcuma longa L.) as a Feed Additive on the Phytochemical Content and Production Performance of Isa Brown Laying Hens - Kasri, Kasri; Radiati, Lilik Eka; Sjofjan, Osfar (Faculty of Animal Science, Universitas Brawijaya, 2024)
The overuse and continuous administration of antibiotics have led to the emergence of resistance, posing challenges in eradicating pathogenic bacteria in poultry digestive tracts. This concern has prompted breeders to seek alternatives, such as turmeric. Turmeric, known for its ability to combat disease-causing microorganisms in the digestive tract and improve livestock performance, is one such herb. This study aimed to assess the impact of fermented turmeric on the phytobiotic content and production performance of laying hens. In the initial phase, turmeric underwent anaerobic fermentation at room temperature for seven days, followed by analysis of curcuminoids and flavonoids. An in vivo study was subsequently conducted with 120 laying hens aged 50 weeks divided into five experimental groups: P0 (basal feed without fermented liquid turmeric) and T1–T4 (basal feed supplemented with fermented liquid turmeric). The results revealed a significant decrease in the curcumin and flavonoid contents after fermentation. Feed consumption increased significantly (P<0.05) but had no significant effect (P>0.05) on hen-day production, egg mass, FCR, or IOFC. numcially decreased FCR values. This study demonstrated that incorporating liquid turmeric into basal feed enhanced production performance while reducing FCR in laying hens. The effect of fermented liquid turmeric on feed consumption was sixty-four percent, and the feed conversion ratio was twenty-four percent. These findings suggest that fermented turmeric can effectively serve as a feed additive in poultry production systems, offering a natural alternative and potentially contributing to sustainable and healthy poultry farming practices